Inceptive Investigation of Audio-Visual Homogenization on Dissociative Neurological Symptoms - Roy, Anney; Girija, Varsha Subramanian (Perceptual and motor skills, 2025)
Dissociative neurological symptom disorder, also called functional neurological symptom disorder or conversion disorder, presents characteristics that are incongruent with medical or neurological conditions. This study investigates whether sensory exposure to red light and white noise can trigger dissociative and conversion symptoms. Consequently, the reported somatosensory alterations significantly challenge current diagnostic protocols. In this study, we record inceptive evidence of conversion symptoms from a sample of 61 healthy university students who reported dissociative states after the Ganzfeld audio-visual homogenization condition. In the Ganzfeld condition, individuals experienced increased conversion and decreased depersonalization when red light and white noise were used as stimuli. Our findings correlate with those of previous studies that highlighted red light's ability to significantly trigger negative effects. Simultaneously, we found that the multimodal Ganzfeld condition may decrease identity confusion. Additionally, dissociative states among these participants were consistent with trauma symptoms, emphasizing the predispositions that may impact executive functioning. We further highlight that the somatosensory alterations may be a result of endogenous and exogenous attentional orientation. This investigation elucidated potential triggers and effects of conversion symptoms that could be important for understanding dissociative psychopathology.
Keywords: dospělí; disociační poruchy; Humans; dissociation; Depersonalization; Conversion Disorder; mladý dospělý; multimodal Ganzfeld; zraková percepce; conversion; mužské pohlaví; Visual Perception; Adult; Dissociative Disorders; Adolescent; Auditory Perception; ženské pohlaví; konverzní poruchy; depersonalizace; lidé; predispositions; mladiství; sluchová percepce; Male; Young Adult; investigation; Female